The Role of trade unions in housing ; regional trade union seminar, Hamburg, 17th-19th January, 1967: supplement to the final report - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development. Manpower and Social Affairs Directorate. Social Affairs Division, 1967)
A seminar series on trade unions in formulating policy in a number of areas. It touches on economic and social programming, including non-wage incomes and prices policy.
contains list of participants.
sju 24/01/2019
Loans
Keywords: Housing; Labor unions